Killfile - Farnsworth, Christopher (William Morrow, an imprint of HarperCollinsPublishers, 2016)
"John Smith possesses a special gift that seems more like a curse: he can access other people's thoughts. He hears the songs stuck in their heads, knows their most private traumas and fears, and relives the painful memories they can't let go of. The CIA honed his skills until he was one of their most powerful operatives, but John fled the Agency and now works as a private consultant, trying to keep the dark potentials of his gift in check--and himself out of trouble. Unfortunately, John is unexpectedly plunged into dangerous waters when his latest client, billionaire software genius Everett Sloan, hires him to investigate a former employee"--Amazon.com.